Algirdui Juliui Greimui – du Semiotica numeriai - Vaitiekūnas, Dainius (Colloquia, 2018)
Semiotica: Journal of the International Association for Semiotic Studies: Semiotica, 2017, Issue 214, Semiotica, 2017, Issue 219: Berlin/Boston: De Gruyter Mouton, ISSN 0037-1998, e-ISSN 1613-3692